Applied welding engineering : - Singh, Ramesh (Butterworth-Heinemann, 2016)
The book’s four part treatment starts with a clear and rigorous exposition of the science of metallurgy including but not limited to: Alloys, Physical Metallurgy, Structure of Materials, Non-Ferrous Materials, Mechanical Properties and Testing of Metals and Heal Treatment of Steels. This is followed by applications: Welding Metallurgy & Welding Processes, Nondestructive Testing, and Codes and Standards.